Analisis Perilaku Etis Akuntan Profesional dalam Perspektif Etika Profesi dan Tanggung Jawab Sosial Perusahaan - Desta Viananda; Sarah Sarah; Tries Ellia Sandari (Journal of Economic and Business Advancement, 2025)
This study examines the ethical behavior of professional accountants through the lens of professional ethics and corporate social responsibility to understand how accountants safeguard the integrity of financial and sustainability information. The growing complexity of financial reporting and ESG disclosures requires accountants to demonstrate a strong ethical commitment, particularly when confronted with business pressures and conflicts of interest that may compromise their independence. The literature indicates that the existence of a professional code of ethics alone does not ensure ethical conduct without the internalization of moral values and the presence of an organizational culture that promotes accountability. Ethical breaches, such as the audit case involving PT Garuda Indonesia Tbk, highlight the urgent need to strengthen professional integrity. Employing a descriptive qualitative approach through a comprehensive literature review, this study identifies the relationship between ethical standards, organizational pressures, and CSR commitments in shaping ethical behavior. The findings emphasize the importance of ethics education, quality control systems, and organizational mechanisms that support transparency and social responsibility to enhance the consistency of accountants’ ethical conduct in Indonesia.